Construction of ecofriendly anticorrosive composite film ZnAl‐LDH by modification of lignin on AA 7075 surface. Issue 10 (13th May 2021) - Cao, Yanhui; Zheng, Dajiang; Lin, Changjian
Abstract: In this study, an environment‐friendly composite ZnAl‐LDH film modified by the rich biomass lignin was prepared on AA 7075 surface successfully. A wide range of characterizations was carried out to obtain the morphology, composition, and structure of this composite film, including scanning electron microscopy, X‐ray diffraction, Fourier transform infrared spectroscopy (FTIR), and so on. In addition, FTIR was used to investigate the complexing interaction between layered double hydroxide (LDH) and lignin. Finally, the corrosion protection ability of this composite film was evaluated by electrochemical impedance spectroscopy in an immersion period of 7 days in NaCl solutions. The results indicated that the ZnAl‐LDH film modified by lignin could provide effective corrosion protection for the underlying substrate in the whole immersion period, with almost one order of magnitude higher of the corrosion resistance in comparison with that in the case of the blank ZnAl‐LDH film after immersion of 7 days. Such results could provide inspiring insights into the development of composite inhibitors based on LDH and biomass. Abstract : Lignin from biomass was used to modify ZnAl‐LDH films on AA 7075 surface, and the obtained composite film was able to provide more effective corrosion protection for the underlying substrate. The IRRAS result was collected to investigate the complexing interaction between lignin and layered double hydroxide (LDH) films, and the result demonstrated that complexing reaction occurred between metal ions of LDH and the functional groups of lignin.